2018
DOI: 10.1242/jcs.210476
|View full text |Cite
|
Sign up to set email alerts
|

Substratum stiffness tunes proliferation downstream of Wnt3a in part by regulating integrin-linked kinase and frizzled-1

Abstract: The Wnt/β-catenin pathway controls a variety of cellular behaviors, aberrant activation of which are associated with tumor progression in several types of cancer. The same cellular behaviors are also affected by the mechanical properties of the extracellular matrix (ECM) substratum, which induces signaling through integrins and integrin-linked kinase (ILK). Here, we examined the role of substratum stiffness in the regulation of cell proliferation downstream of Wnt3a. We found that treatment with Wnt3a increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…We previously found that stably depleting ILK using short hairpin RNA (shRNA) leads to a striking change in the morphology of NMuMG mouse mammary epithelial cells ( Figure 1, A and B ) ( Han et al. , 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously found that stably depleting ILK using short hairpin RNA (shRNA) leads to a striking change in the morphology of NMuMG mouse mammary epithelial cells ( Figure 1, A and B ) ( Han et al. , 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…, 2010 ). Given that stiff microenvironments up-regulate the expression of ILK ( Han et al. , 2018 ), it is possible that stiff matrices prime cells to undergo EMT through ILK-mediated signaling through Snail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous research uncovered sunitinib's actions on the brain tumor microenvironment impedes brain tumor progression 21. FZD1 could also get involved in cellular microenvironment in the regulation of cell proliferation 22. There was a report that FZD1 expression in the tumor microenvironment had a gradient effect may modulate colon cancer progression and dissemination, representing a new therapeutic target for patients with colon cancer 23.…”
Section: Introductionmentioning
confidence: 99%
“…In general, in spite of several studies assessing the biological effect of substrate stiffness [ 194 , 195 , 209 216 ], cytoskeletal trafficking/structural changes in cells encapsulated in biomaterials of different stiffness has been scarcely investigated, with no consensus having been reached as yet. Further research on this direction is limited by the fact that biomaterial stiffness influences several other different processes, including biomaterial degradation rate, cellular infiltration, migration and proliferation rate.…”
Section: Main Textmentioning
confidence: 99%